Trans‐generational maternal effect: temperature influences egg size of the offspring in Atlantic salmon Salmo salar. Issue 2 (28th June 2016) - Jonsson, B.; Jonsson, N.
Abstract : Effect of increased temperature during egg maturation on the mass of single eggs produced by the offspring was investigated experimentally in Atlantic salmon Salmo salar . Mass of eggs produced by next‐generation females was larger when their mothers experienced warmer water during the last two months of egg maturation, relative to those that experienced unheated river water. There was no similar trans‐generational paternal effect on offspring egg mass.